System Decision of Natural Disaster Logistics (Case Study of Mount Agung Eruption) - Pradipta, I Made Dhanan; Pradnya Pramita, Made Dinda; Janardana, I Gusti Ngurah (International Journal of Engineering and Emerging Technology, 2018)
Gunung Agung is one of the most potent eruption volcanoes in Indonesia. Reflecting back to 1963 when Mount Agung erupted, the impact was so devastating. Even the impact for months. The lack of food supplies is becoming a central job for the government. The distribution of logistics plays an important role in this regard whether it is food, clothing or other necessities, but the current logistics distribution system is still manual so it is not very efficient and very likely there is a misstatement. The impact of difficulties in managing logistical assistance can be seen, eg uneven distribution of relief goods in terms of number of inter-regions (posts), types of relief items sent are not in accordance with the type desired by individual posts, and especially for fast food, then damaged and outdated because it was sent to the post at the wrong time and improper handling. Needed a solution to minimize the problems that arise in the process of disbursing logistics disaster management is by using the Logistics Management Information System. In this research, the method used using two methods, namely waterfall method for system development, and for decision support system using Topsis method Expected to be able to manage logistical support in a timely, timely, and precise location